1972
DOI: 10.2307/1934772
|View full text |Cite
|
Sign up to set email alerts
|

Sceloporus Undulatus: A Study of the Intraspecific Comparative Demography of a Lizard

Abstract: Population studies were conducted on the eastern fence lizard in South Carolina, Texas, Ohio, and Colorado. Hatching occurs in early to middle summer and well into the fall in southern populations, but is restricted to late summer and early fall in Colorado and Ohio. The hatchlings in Texas reach a mature size in 3 months and these lizards, as well as those in South Carolina, reproduce before they are a year old. In Colorado and Ohio the lizards do not mature until almost 2 years of age, but at a larger size t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
193
1
3

Year Published

1981
1981
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(201 citation statements)
references
References 15 publications
4
193
1
3
Order By: Relevance
“…The Quality of Young Model (QYM).-We make the same assumptions that we used to build the Salamander Model, but we also specify that fecundity is a constant for all ages at maturity, We used published data on salamanders (Tilley, 1979) and lizards (Blair, 1960;Tinkle, 1967;Tinkle and Ballinger, 1972;Vinegar, 1976) for the estimates of the constants. There are serious problems with inferring these parameters from the available data, for they require that one know what fecundity or mortality would have been if the organism had matured at a different age.…”
Section: H*mentioning
confidence: 99%
“…The Quality of Young Model (QYM).-We make the same assumptions that we used to build the Salamander Model, but we also specify that fecundity is a constant for all ages at maturity, We used published data on salamanders (Tilley, 1979) and lizards (Blair, 1960;Tinkle, 1967;Tinkle and Ballinger, 1972;Vinegar, 1976) for the estimates of the constants. There are serious problems with inferring these parameters from the available data, for they require that one know what fecundity or mortality would have been if the organism had matured at a different age.…”
Section: H*mentioning
confidence: 99%
“…Life histories have been documented in many disjunct populations throughout its range, and some life-history phenotypes vary more than twofold among populations (reviewed by Tinkle and Ballinger 1972;Tinkle and Dunham 1986;Gillis and Ballinger 1992;Niewiarowski 1994). Comparative, experimental, and theoretical studies have suggested many hypotheses (adaptive and nonadaptive) to account for this geographic variation in life histories (Stearns and Crandall 1981;Grant and Porter 1992;Adolph andPorter 1993, 1996;Niewiarowski 1994Niewiarowski , 2001Angilletta 2001).…”
Section: Study Speciesmentioning
confidence: 99%
“…1977;Baxter andStone 1980. Habitat utilization: Tanner 1965;Ferguson 1971;Tinkle 1972;Tinkle and Ballinger 1972;Werth 1972;Ferner 1974Ferner , 1976Turner 1974;Baxter and Stone 1980;Jones and Droge 1980;Waldschmidt 1980;Hammerson andLanglois 1981. Feeding: Woodbury 1932;Johnson 1966;Werth 1972;Turner 1974;Ferner 1976;Baxter andStone 1980.…”
Section: Sceloporus Undulatus Eastern Fence Lizardmentioning
confidence: 99%
“…Feeding: Woodbury 1932;Johnson 1966;Werth 1972;Turner 1974;Ferner 1976;Baxter andStone 1980. Breeding: Ferguson 1971;Tinkle 1972;Tinkle and Ballinger 1972;Turner 1974;Derickson 1976;Ferner 1976;Baxter and Stone 1980;Ferguson et al . 1980;Ballinger et al 1981.…”
Section: Sceloporus Undulatus Eastern Fence Lizardmentioning
confidence: 99%